Economies and employment in growing and declining urban peripheries in South Africa. (August 2021) - Todes, Alison; Houghton, Jennifer
Urban peripheral growth takes diverse forms, including the development of new economic centralities, raising questions about access to employment for residents, especially in contexts where unemployment is high and economies are shifting towards more skilled and service-related employment. This article explores two case studies of residents' experience of access to employment close to economic centralities on the urban edge in South Africa: the growing northern eThekwini area (Durban), which has developed major retail and office complexes since the 1990s and more recently a new airport and industrial spaces, and a declining industrial decentralisation point established in the 1980s on the eastern edge of the City of Tshwane (Pretoria). It shows the severe impact of industrial decline in the Tshwane case, but while unemployment is less in northern eThekwini, access to employment for low-income residents in these areas is still very limited and constrained. Experiences are however differentiated, suggesting a complexity of outcomes. The cases point to the vulnerability of these economic centralities to economic change and the limits of new developments on the urban periphery to addressing unemployment. These findings have implications for the current advocacy of 'new cities' in economic contexts such as South Africa.